2016
DOI: 10.18632/oncotarget.7710
|View full text |Cite
|
Sign up to set email alerts
|

Hypotaurine evokes a malignant phenotype in glioma through aberrant hypoxic signaling

Abstract: Metabolomics has shown significant potential in identifying small molecules specific to tumor phenotypes. In this study we analyzed resected tissue metabolites using capillary electrophoresis-mass spectrometry and found that tissue hypotaurine levels strongly and positively correlated with glioma grade. In vitro studies were conducted to show that hypotaurine activates hypoxia signaling through the competitive inhibition of prolyl hydroxylase domain-2. This leads to the activation of hypoxia signaling as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 54 publications
3
29
0
Order By: Relevance
“…The differential expression analysis also identified signaling pathways responding to hypoxia and their key regulators. Several of these pathways are associated with HIF-1α, in agreement with findings of other groups [60][61][62][63]. However, several of the proteins reversing the effect of hypoxia with drug had lower fold-changes upon treatment with CyA.…”
Section: Discussionsupporting
confidence: 90%
“…The differential expression analysis also identified signaling pathways responding to hypoxia and their key regulators. Several of these pathways are associated with HIF-1α, in agreement with findings of other groups [60][61][62][63]. However, several of the proteins reversing the effect of hypoxia with drug had lower fold-changes upon treatment with CyA.…”
Section: Discussionsupporting
confidence: 90%
“…The differential expression analysis identified signaling pathways responding to hypoxia and their key regulators. Several of the identified pathways are associated with HIF-1α, in consensus with the previous literature (70)(71)(72)(73). However, several of the proteins reversing the effect of hypoxia with drug had lower fold-changes upon treatment with CyA.…”
Section: Discussionsupporting
confidence: 87%
“…Taurine can cross the blood brain barrier (BBB) and involves in a wide array of physiological phenomena including inhibitory neurotransmission, long-term potentiation in the striatum/hippocampus, and possible protection against glutamate excitotoxicity and prevention of epileptic seizures [46474849]. Interestingly, recent studies on glioma have shown that hypotaurine interferes with hypoxia signaling, leading to malignant phenotypes [5051]. Hypotaurine acts as a competitive inhibitor to activate signals in prolyl hydroxylase domain-2 (PHD2), which regulates hypoxia signals.…”
Section: Discussionmentioning
confidence: 99%